Geochemistry and Petrographical Study of Langrial Iron Ore from Tethyan Hazara Area Pakistan, with Emphasis on its Economic Characterization and Depositional Setting - Naghmah Haider; Sajjad Khan; Mehboob Ur Rashid; Rehan ul Haq Siddiqui; Jawad Zeb; Shahid Iqbal; Asad Khan; Waqas Ahmad (International Journal of Economic and Environment Geology, 2018)
The Langrial iron ore of Hazara area has been studied in detail at five locations for its geochemistry, genesis and economic potential investigations. A maximum of thirty samples were collected from iron ore bodies at different localities of Bagnotar, Danna Noral, TattiMaira, Najafpur and Jabri for detailed analysis. The thick bedded iron ore has been deposited in the form of unconformity at Cretaceous-Paleocene boundary sandwiched between Kawagarh and Hangu formations (i.e. Cretaceous-Paleocene boundary). At the base of Hangu Formation variable thickness of these lateritic beds spread throughout the Hazara and Kohat-Potwar plateau. These iron ore bodies are studied by X-Ray Diffraction technique (XRD), X-ray Fluorescence Spectrometry (XRF), Petrographic studies and Scanning Electron Microscope (SEM). This XRD analysis indicated that iron bearing minerals are hematite with intercalation of chamosite, quartz and a proportion of impurities having albite, illite-montmorillonite, kaolinite, calcite, dolomite and ankerite. The X-ray Fluorescence (XRF) results show that total Fe2O3 ranges from 30 to 50% having high silica, while alumina to silica ratio is less than 1. The petroghraphic studies revealed concentration of Langrial iron beds as oolitic hematite nodule having variable concentric to composite structure. A high energy shallow marine depositional environment was deduced for Langrial iron ore, as inferred from SEM and mineralogical data. The overall results show that Langrial iron ore is a low-grade iron ore with average Fe2O3of 52%, and can be upgraded by applying modern mining techniques to fulfill steel requirements of the country.